2022
DOI: 10.3390/biom12020176
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulated Epicardial Adipose Tissue as a Risk Factor and Potential Therapeutic Target of Heart Failure with Preserved Ejection Fraction in Diabetes

Abstract: Cardiovascular (CV) disease and heart failure (HF) are the leading cause of mortality in type 2 diabetes (T2DM), a metabolic disease which represents a fast-growing health challenge worldwide. Specifically, T2DM induces a cluster of systemic metabolic and non-metabolic signaling which may promote myocardium derangements such as inflammation, fibrosis, and myocyte stiffness, which represent the hallmarks of heart failure with preserved ejection fraction (HFpEF). On the other hand, several observational studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 220 publications
(230 reference statements)
0
16
0
Order By: Relevance
“…The reduced mass and inflammation of perivisceral adipose tissue induced by SGLT2-Is may minimize the inflammatory paracrine actions on visceral organs such as the heart and kidney to promote cardiac fibrosis and renal glomerulosclerosis [ 263 ]. In particular, SGLT2-Is exert a drug class effect of reduction of epicardial adipose tissue, the true visceral fat of heart, associated with attenuated inflammation and less secretion of deleterious adipokines, that can positively affect both structure and function of adjacent myocardium [ 264 , 265 ]. A particularly relevant role seems to be played by attenuation of leptin secretion and related paracrine effects [ 266 , 267 ].…”
Section: Anti-inflammatory and Anti-oxidant Effects Of Sglt2-ismentioning
confidence: 99%
“…The reduced mass and inflammation of perivisceral adipose tissue induced by SGLT2-Is may minimize the inflammatory paracrine actions on visceral organs such as the heart and kidney to promote cardiac fibrosis and renal glomerulosclerosis [ 263 ]. In particular, SGLT2-Is exert a drug class effect of reduction of epicardial adipose tissue, the true visceral fat of heart, associated with attenuated inflammation and less secretion of deleterious adipokines, that can positively affect both structure and function of adjacent myocardium [ 264 , 265 ]. A particularly relevant role seems to be played by attenuation of leptin secretion and related paracrine effects [ 266 , 267 ].…”
Section: Anti-inflammatory and Anti-oxidant Effects Of Sglt2-ismentioning
confidence: 99%
“…Individuals with type 2 diabetes (T2D) are at a high risk of developing heart failure with preserved ejection fraction (HFpEF), a heterogeneous and complex syndrome that, despite its growing prevalence and incidence with significant morbidity and mortality, still retains important knowledge gaps and therapeutic challenges 1 . In recent years, excessive epicardial adipose tissue (EAT) has been regarded as a one among the main actors in myocardial disease by promoting inflammation, micro‐vasculopathy, fibrosis and stiffness of myocardium, all findings corresponding to the hallmarks of HFpEF 2 . Its quantification is easy and reproducible during standard transthoracic echocardiography 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Another explanatory concept is the decrease in epicardial fat caused by leptin downregulation [ 128 , 133 ]. Epicardial adipose tissue growth is linked to poor left ventricular relaxation and diastolic filling, either directly through constriction or indirectly through the regulation of pro-inflammatory molecule release, resulting in inflammation, microcirculatory dysfunction, and fibrosis [ 134 ]. SGLT2 expression has been established in human epicardial adipose tissue, and the majority of the data on individuals with type 2 DM show a decrease in epicardial adipose tissue mass after SGLT2 inhibition [ 134 , 135 ].…”
Section: A Novel Era In Heart Failure Pharmacotherapy: Sglt2 Inhibitorsmentioning
confidence: 99%
“…Epicardial adipose tissue growth is linked to poor left ventricular relaxation and diastolic filling, either directly through constriction or indirectly through the regulation of pro-inflammatory molecule release, resulting in inflammation, microcirculatory dysfunction, and fibrosis [ 134 ]. SGLT2 expression has been established in human epicardial adipose tissue, and the majority of the data on individuals with type 2 DM show a decrease in epicardial adipose tissue mass after SGLT2 inhibition [ 134 , 135 ]. The newly published randomized, placebo-controlled EMPA-TROPISM study found that empagliflozin decreased epicardial fat content in individuals without T2DM, HF, and a lower LVEF [ 128 ].…”
Section: A Novel Era In Heart Failure Pharmacotherapy: Sglt2 Inhibitorsmentioning
confidence: 99%